Perancangan Interior Pusat Komunitas Game Dota di Surabaya - Andereas Pandu Setiawan, Ronald Gondosiswanto (Intra, 2013)
Game Dota already known the game lovers in the world since 2005. Dota game was made because the developers wanted to simplify the predecessor game (Warcraft III: Frozen Throne) the genre of real-time strategy towards real-time action (Dota) with gameplay simpler and attract the interest of gamers in the world, particularly gamers adolescents. Therefore, to help those who have a hobby like this, we need a vessel that is really capable of uniting them in a relationship together in the Dota game play directly or indirectly.